2017
DOI: 10.4236/jcdsa.2017.74026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of a Mesotherapy Formulation for Skin Rejuvenation in Healthy Volunteers

Abstract: Mesotherapy is a mildly invasive procedure involving several subcutaneous drug injections, which are performed simultaneously. The concept is to inject a very small amount of active compounds (hyaluronic acid, vitamins, antioxidants, enzymes, humectants, …) and the aim is to stimulate the biosynthetic capacity of fibroblasts, increase collagen and elastin production and to give active essential molecules for a fibroblasts environment. Numerous studies suggest that the mesotherapy procedure improves skin hydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…10 Biophysical measurements and colorimetry showed improvement in both superficial and deep skin hydration, erythema, PH of skin, and sebum produc tion. [1][2][3][6][7][8][9]11,12,14 Histological and ultrasound evaluation confirmed clinicopathological and biophysical improvements was confirmed to continue up to 3 months by some studies. [1][2][3][6][7][8][9]11,12,14 In contrast, four studies revealed no significant improvement in clinical or histological features of skin with different compounds of mesococktail.…”
Section: Treatment Characteristics and Injection Techniquesmentioning
confidence: 93%
See 2 more Smart Citations
“…10 Biophysical measurements and colorimetry showed improvement in both superficial and deep skin hydration, erythema, PH of skin, and sebum produc tion. [1][2][3][6][7][8][9]11,12,14 Histological and ultrasound evaluation confirmed clinicopathological and biophysical improvements was confirmed to continue up to 3 months by some studies. [1][2][3][6][7][8][9]11,12,14 In contrast, four studies revealed no significant improvement in clinical or histological features of skin with different compounds of mesococktail.…”
Section: Treatment Characteristics and Injection Techniquesmentioning
confidence: 93%
“…[1][2][3][6][7][8][9]11,12,14 Histological and ultrasound evaluation confirmed clinicopathological and biophysical improvements was confirmed to continue up to 3 months by some studies. [1][2][3][6][7][8][9]11,12,14 In contrast, four studies revealed no significant improvement in clinical or histological features of skin with different compounds of mesococktail. Although electron microscopy showed neocollagenesis of smaller caliber collagen fibers, but the result was not statistically significant.…”
Section: Treatment Characteristics and Injection Techniquesmentioning
confidence: 94%
See 1 more Smart Citation
“…1 The greatest immediately clinical effects observed after facial biorevitalization are reduction of wrinkles, the improvement of deep hydration, firmness, uniformity, and radiance of the complexion. 2,3 In recent years, dermal fillers that became the material of choice are HA-based fillers for use in soft tissue and dermal correction and mostly replacing collagen fillers. 4,5 Hyaluronic acid is widely used in anti-aging products, either in native form in products to be injected by skin biorevitalization techniques or cross-linked in dermal fillers.…”
Section: Introductionmentioning
confidence: 99%
“…В этом плане лидирующие позиции принадлежат инъекционной косметологии. Особое место и популярность мезотерапии в эстетической медицине обусловлены возможностью патогенетического подхода к решению косметических проблем, связанных, прежде всего, со старением кожи [4,7,9]. Старение кожи -постепенный процесс, обусловленный функциональными и структурными изменениями, а возможность противодействия посредством восстановления состояний кожи с помощью биоактивных пептидов заслуживает самый присталь-ный интерес.…”
Section: Introductionunclassified